Characterization of spray-coated ZnO buffer layer for inverted polymer solar cells. (December 2017) - Wu, Fan; Li, Zidong; Yang, Dalei; Huan, Yan; Wang, Jie; Yang, Xiaoniu
Graphical abstract: Highlights: Inverted polymer solar cells are based on ultrasonic spray-coated ZnO buffer layer. Optical scattering property of ZnO film dramatically influence device performance. Suitable film thickness and annealing temperature for ZnO film are found. A high power conversion efficiency of 6.7% is achieved. Abstract: The influences of optical scattering property, film thickness and annealing temperature of zinc oxide (ZnO) buffer layers on the performance of inverted polymer solar cells were systematically investigated. The ZnO films were prepared by ultrasonic spray coating, and the optical scattering property was manipulated by the precise adjustment of the operation conditions. It was found that the higher diffusive transmission of the ZnO film resulted in the higher short circuit current but the lower power conversion efficiency (PCE). With the optimum spray parameters, the suitable film thickness and annealing temperature for ZnO buffer layers were found, and the PCE of the corresponding inverted PSCs reached to 6.7%. This study is highly valuable in the technology transfer of polymer solar cells from lab to industry.